Infection with very virulent infectious bursal disease virus causes infiltration of t cells into bursa of fabricius - Jamil, Aimi Zulfadli; Swee, Keong Yeap; Omar, Abdul Rahman; Mohammed Alitheen, Norjahan Banu (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
Infectious bursal disease (IBD) is an immunosuppression disease, causing high mortality rate in young chickens and instigated by Infectious Bursal Disease Virus (IBDV). Numerous studies have shown that IBDV can infect B cells and induce apoptosis. However, the effect of the virus on T cell is not clear. This finding provides evidence that IBDV induce infiltration of CD4 and CD8 T cells into bursa during acute phase of the infection.